ApoE4 lowers age at onset in patients with frontotemporal dementia and tauopathy independent of amyloid‐β copathology. Issue 1 (19th March 2019) - Koriath, Carolin; Lashley, Tammaryn; Taylor, William; Druyeh, Ronald; Dimitriadis, Athanasios; Denning, Nicola; Williams, Julie; Warren, Jason D.; Fox, Nick C.; Schott, Jonathan M.; Rowe, James B.; Collinge, John; et al.
Abstract: Introduction: Apolipoprotein E (ApoE) is the most important genetic risk factor for Alzheimer's disease (AD), with ApoE4 thought to enhance and accelerate amyloid‐β (Aβ) pathology. ApoE4 has recently been described to increase neurodegeneration in a mouse model of frontotemporal dementia (FTD), in vitro, and in patients, demonstrating that ApoE4 modifies tauopathy independently of Aβ. This raises the question whether ApoE genotype also modifies the clinical phenotype in patients with FTD with tau pathology. Methods: We analyzed 704 patients with FTD, including a genetically and neuropathologically confirmed subset, and 452 healthy elderly controls. We compared ApoE4 genotype frequency and age at onset in tau+ or TDP43+ FTD patients with or without Aβ copathology. Results: The ApoE4 genotype lowered age at onset in patients with FTD and tau pathology, particularly once accounting for confounding effects of Aβ pathology. Discussion: We conclude that ApoE4 accelerates neurodegeneration in FTD patients with MAPT mutations or FTLD‐tau pathology, independent of Aβ.